2015
DOI: 10.1038/ejcn.2015.76
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of lifestyle behaviours and relation to body composition in European children. The IDEFICS study

Abstract: Clusters characterised by high sedentary behaviour, low F&V and SSB consumption and low PA turned out to be the most obesogenic factors in this sample of European children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 35 publications
5
68
2
Order By: Relevance
“…26 The score was assigned according to the percentage of children and youth participating in some type of sport out-of-school at least once a week. Seven percent of males and 6% of females aged 2 to 5 years met the recommendation; the percentage increased to 46% and 28% for males and females aged 6 to 9 years, respectively.…”
Section: Organized Sports Participation: Bmentioning
confidence: 99%
See 2 more Smart Citations
“…26 The score was assigned according to the percentage of children and youth participating in some type of sport out-of-school at least once a week. Seven percent of males and 6% of females aged 2 to 5 years met the recommendation; the percentage increased to 46% and 28% for males and females aged 6 to 9 years, respectively.…”
Section: Organized Sports Participation: Bmentioning
confidence: 99%
“…Seven percent of males and 6% of females aged 2 to 5 years met the recommendation; the percentage increased to 46% and 28% for males and females aged 6 to 9 years, respectively. 26 For older children, data from the 2013 ALADINO study indicated that 71% of males and 61% of females aged 7 and 8 years did some type of sport at least once a week. 11 Adolescents' data referred to the percentage of individuals doing some type of organized PA, with 64% of young adolescents meeting the guidelines (74% male and 54% female) and only 50% of 16-to 18-year-old adolescents achieving the recommendations (64% male and 35% female).…”
Section: Organized Sports Participation: Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study showed that male students may be likely to spend more time using computers than female students, reducing their time spent participating in physical activities. Nevertheless, there is no conclusive results to this observation as for example in Santaliestra-Pasías et al (2015) discussion, dietary patterns, physical activity and sedentary behaviours are some of the main behavioural determinants of obesity. The sexual maturation could be another reason for the high level of BMI among male students.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding EBRBs, consumption of energy-dense foods, low levels of physical activity, and increased sedentary time have been reported to be independently associated with an increased childhood obesity risk [12,13]. Similar to perinatal risk factors, EBRBs seem to be influenced also by regional and sociodemographic variations [7,14].…”
Section: Introductionmentioning
confidence: 99%